Malignant Nodular Hidradenoma: Isolated Case Report and Review of Literature - Khan, Sadia Armin; Ali, Abu Ahmed Ashraf; Ferdousi, Shamima; Riyad, Mahmud; Mahmud, Ahmed Al Hasan (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Malignant Nodular Hidradenoma is an infrequent highly malignant, primary skin tumor derived from eccrine sweat glands. It has an aggressive course, with high recurrence, high rate of metastases and has very poor prognosis. It has been described as an orphanneoplasm. The tumor is similar to its benign counterpart but had additional features such as surface ulceration, numerous mitotic figures and infiltrative growth pattern. Pre-operative diagnosis is difficult by the fine needle aspiration cytology. Malignant nodular hidradenoma of chest wall in 35 years old women, who presented to us with a recurrent rapidly growing swelling over chest wall that grew rapidly over two months after first excision. Tissue diagnosis of first excised specimen was eccrine poroma that was similar to its benign counterpart. J Bangladesh Coll Phys Surg 2016; 34(2): 100-103